Innovating Community-Based Drinking Water Treatment: A Mobile Device in Barangay Lupa, Compostela, Cebu (International Journal of Scientific Research and Management (IJSRM), 2024)
In response to the significant issue of insufficient access to safe drinking water in the mountainous barangay of Lupa, Compostela, Cebu, this study provides a customized mobile water treatment device that seeks to address current drinking water issues, providing mitigation to the community. The treated water undergoes rigorous laboratory testing to determine the device’s treatment performance on deep-well water sources in the barangay. This study evaluated the device’s acceptability level, performance, and potential weaknesses using weighted mean calculations, microbial contamination calculations, and Failure Mode and Effects Analysis (FMEA). The results reveal a significant level of acceptance among respondents toward adopting the mobile water treatment device. Moreover, the device’s treated water effectively meets the 2017 Philippine National Drinking Water Standards, making it safe for drinking. However, observation highlights device vulnerabilities, particularly the water pump’s tendency to overheat and the UV sterilizer’s sensitivity, emphasizing the importance of consistent monitoring and maintenance practices.